Dis-comforting Urban Myths: Challenging Brexit Nostalgia in Recent Edinburgh Fiction - Jones, Carole (Complutense Journal of English Studies, 2021)
This article analyses two contemporary novels, Mary Paulson-Ellis’ The Other Mrs Walker (2016) and Ever Dundas’ Goblin (2017), comparing their depictions of Edinburgh in their strikingly similar parallel narratives, in which a contemporary Edinburgh setting intertwines with that of London in the Second World War. In the context of the Brexit vote of 2016, in which arguments for British autonomy and border closure won the day, the article argues that these texts challenge the pro-Brexit discourse which employed the mythology of the Blitz spirit to undermine the backward-looking nostalgia of a specifically English nationalism. In contrast, the Scottish setting of Edinburgh is presented here as facilitating a turn to a future of more mobile narratives of interrelation and connectedness rather than the fixed dimensions of myth